Tumor suppressor gene ARMC5 controls adrenal redox state through NRF1 turnover. Issue 11 (30th September 2022) - Cavalcante, Isadora P; Rizk-Rabin, Marthe; Ribes, Christopher; Perlemoine, Karine; Hantel, Constanze; Berthon, Annabel; Bertherat, Jérôme; Ragazzon, Bruno
Abstract : ARMC5: is a tumor suppressor gene frequently mutated in primary bilateral macronodular adrenal hyperplasia (PBMAH), an adrenal cause of Cushing's syndrome. The function of ARMC5 is poorly understood, aside from the fact that it regulates cell viability and adrenal steroidogenesis by mechanisms still unknown. Tumor suppressor genes play an important role in modifying intracellular redox response, which in turn regulates diverse cell signaling pathways. In this study, we demonstrated that inactivation in adrenocortical cells increased the expression of actors scavenging reactive oxygen species, such as superoxide dismutases (SOD) and peroxiredoxins (PRDX) by increasing the transcriptional regulator NRF1. Moreover, ARMC5 is involved in the NRF1 ubiquitination and in its half-life. Finally, inactivation alters adrenocortical steroidogenesis through the activation of p38 pathway and decreases cell sensitivity to ferroptosis participation to increase cell viability. Altogether, this study uncovers a function of ARMC5 as a regulator of redox homeostasis in adrenocortical cells, controlling steroidogenesis and cell survival.